Modified β-glucans promote saponin and fucosylated chondroitin sulfate biosynthesis in sea cucumber Apostichopus japonicus in association with activation of the TLR-MAPK signaling pathway - Zezheng Qi; Zeyu Zhang; Wenyue Dai; Hongmei Ma; Junpeng Ge; Yutong Yu; Mengling Cheng; Wenjian Zhao; Shihui Pan; Min Gu; Nan Bai (Fish & Shellfish Immunology, 2026)

Hawthorn Polysaccharide Enhances Growth, Immunity, and Intestinal Health in Crucian Carp (Carassius auratus) Challenged with Aeromonas hydrophila - Liang Luo; Zhigang Zhao; Shihui Wang; Rui Zhang; Kun Guo; Cheng Zhao; Baoquan He; Wei Wang; Wenhua Wu (Fishes, 2025)
Bacterial disease infections pose a major challenge to the healthy growth of crucian carp. Hawthorn polysaccharide (HP) is a natural active ingredient in hawthorn and has a wide range of pharmacological effects. However, the mechanism of HP against Aeromonas hydrophila infection in crucian carp cultures is unknown. In this study, it was found that 0.4% HP could significantly reduce the mortality of crucian carp, significantly increase the activities of T-AOC, SOD, CAT, and GSH-PX of crucian carp infected with A. hydrophila (p

Exposure to benzotriazole UV stabilizer-329 at environmental concentrations induces neurotoxicity by affecting neurotransmission in Caenorhabditis elegans - Yunjiang Yu; Hongzhi Guo; Shihui Tan; Huiyang Wang; Yao Dang; Haibo Chen; Qi Zhuang; Cheng Ding; Mingdeng Xiang (Environmental Pollution, 2025)

Corrigendum to “Evolution of bacterial flora in raw yak milk and its effect on quality characteristics during frozen storage” [Volume 463, Part 3, 15 January 2025, 141367]. - Sijia Yang; Wenjia Zhou; Shihui Cheng; Jingwen Zhao; Zekun Yuan; Jianing Zhai; Libo Liu; Aili Li; Peng Du (Food Chemistry, 2025)

Optimized pretreatment strategies for enhanced isolation and functional preservation of bovine milk exosomes - Aili Li; Shihui Cheng; Sufang Duan; Yumeng Zhang; Jian He; Chun Li; Guofang Zhang (Food Bioscience, 2025)

Inner Mitochondrial Membrane Peptidase 2-Like Deletion Aggravates Mitochondrial Apoptosis and Inhibits Autophagy After Hyperglycemia Stroke - Ning Ma; Xiaohong Luo; Jianan Wang; Shihui Sun; Ruimin Liang; Zijing Zhang; Zhengyi Cheng; Jinlian Wang; Yi Ma (Molecular Neurobiology, 2025)

Cooperation of Lactoplantibacillus plantarum and polyethylene microplastics facilitated the disappearance of tetracycline during anaerobic fermentation of whole plant maize - Yubo Zhang; Pan Wang; Yu Tang; Chaosheng Liao; Xiaolong Tang; Pai Hou; Cheng Chen; Xiaokang Huang; Guangrou Lu; Lin Li; Mingjie Zhang; Fuxiang Li; et al. (Journal of Hazardous Materials, 2025)

Evolution of bacterial flora in raw yak milk and its effect on quality characteristics during frozen storage - Sijia Yang; Wenjia Zhou; Shihui Cheng; Jingwen Zhao; Zekun Yuan; Jianing Zhai; Libo Liu; Aili Li; Peng Du (Food Chemistry, 2025)

In vitro simulated digestion of different heat treatments sweet potato polysaccharides and effects on human intestinal flora - Chuan Liu; Yu Miao; Jingwen Zhao; Sijia Yang; Shihui Cheng; Wenjia Zhou; Wenkui Guo; Aili Li (Food Chemistry, 2025)

Submarine Morphological Description of the Ancient Archipelagic Aprons in the Marcus–Wake Seamount Group, Northwestern Pacific Ocean - Xiao Wang; Huaiming Li; Yongshou Cheng; Pengfei Yao; Fengyou Chu; Weilin Ma; Hongyi Wang; Shihui Lv; Xiaohu Li; Zhenggang Li; Weiyan Zhang; Yanhui Dong (Journal of Marine Science and Engineering, 2024)
Herein, the morphological characteristics of submarine archipelagic aprons were presented for five guyots, Suda, Arnold, Lamont, Niulang, and Zhinyv, which are over 80 Ma years old and are located in the Marcus–Wake seamount group, northwestern Pacific Ocean. Nearly 28 landslide deposits were recognized using the bathymetry and backscatter intensity data collected from the studied guyots. Landslides and their deposits that surround seamounts are mostly related to the morphology of debris avalanches, scarps, gullies/channels, and bedforms. The morphology of the archipelagic aprons of the studied guyots indicates mutual landslide processes, including slump and distinct debris avalanches arising from a cohesive or cohesionless landslide material flow. The superimposition of debris flows and sedimentation dominates the recent stages of the studied guyots. The archipelagic aprons corresponding to convex-arc-shaped scarps exhibit larger domains compared to the invagination-arc-shaped scarps with similar lateral lengths. The scarp morphologies of the studied guyots are predominantly of the complex-arc shape, indicating multiple landslide events. Parallel and convergent gullies and channels are mostly found on the elongated landslide deposits, whereas divergent and radial gullies and channels are mostly distributed on the fan-shaped aprons. Ubiquitous sediment waves occurred on the bedforms of the distal archipelagic apron across the studied guyots because of sediment creep. Small-scale sediment waves were only observed in the channels on the aprons of the Suda guyot.

Workability of low-density polyethylene modified asphalt mixtures: A statistical analysis of particle kinematics - Shuai Yu; Jubair Ahmad Musazay; Cheng Zhang; Pengsen Hu; Shihui Shen (Journal of Cleaner Production, 2024)

Quantitative trait loci detection for three tiller-related traits and the effects on wheat (Triticum aestivum L.) yields - Yibiao Cai; Xiaohan Zhou; Chenyang Wang; Aifeng Liu; Zhencang Sun; Shihui Li; Xinyao Shi; Shuang Yang; Yuxiang Guan; Jiajia Cheng; Yongzhen Wu; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Progress of research on the alleviation of intestinal inflammation by regulating intestinal mucosal function with postbiotics - Aili Li; Sijia Yang; Xueting Han; Chuan Liu; Jie Zheng; Yiming Ma; Shihui Cheng; Jingwen Zhao; Wenjia Zhou; Peng Du (Food Bioscience, 2024)

Characterization and fine mapping analysis of a major stable QTL qKnps-4A for kernel number per spike in wheat - Ran Qin; Tianhang Ma; Yibiao Cai; Xinyao Shi; Jiajia Cheng; Jizi Dong; Chenyang Wang; Shihui Li; Guoqing Pan; Yuxiang Guan; Lei Zhang; Shuang Yang; et al. (Theoretical and Applied Genetics, 2023)

Chronic Psychological Stress Disrupts Iron Metabolism and Enhances Hepatic Mitochondrial Function in Mice - Shihui Guo; Yingying Dong; Xiaoxian Cheng; Zijin Chen; Yingdong Ni; Ruqian Zhao; Wenqiang Ma (Biological Trace Element Research, 2023)

High-throughput screening of metal–organic frameworks for hydrogen purification - Shihui Wang; Min Cheng; Lei Luo; Xu Ji; Chong Liu; Kexin Bi; Li Zhou (Chemical Engineering Journal, 2023)

High-throughput virtual screening of metal–organic frameworks for xenon recovery from exhaled anesthetic gas mixture - Min Cheng; Shihui Wang; Zhiyuan Zhang; Li Zhou; Chong Liu; Yiyang Dai; Yagu Dang; Xu Ji (Chemical Engineering Journal, 2023)

Late Mesozoic rifting and its deep dynamic mechanisms in the central Sulu orogenic belt: Records from Lingshan Island - Tengfei Zhou; Yaoqi Zhou; Nina Søager; Paul Martin Holm; Zhenkai Zhang; Jun Wang; Zhao Liang; Hongyu Mu; Yanjun Cheng; Feifei Liu; Miao Wang; Yue Zhang; et al. (Science China Earth Sciences, 2022)

Evaluation of the inhibitory effects of four different microecological preparations on Cladophora - Jian Liu; Yunfei Sun; Wenfeng Han; Jinghao Li; Shihui Wang; Zhigang Yang; Yongxu Cheng (Aquaculture International, 2022)

Effects of telomere length on leukemogenesis - Shihui Ma; Guohuan Sun; Shangda Yang; Zhenyu Ju; Tao Cheng; Hui Cheng (Science China Life Sciences, 2020)

A Carbon Footprint of High‐Speed Railways in China: A Case Study of the Beijing‐Shanghai Line - Jianyi Lin; Huimei Li; Wei Huang; Wangtu(Ato) Xu; Shihui Cheng (Journal of Industrial Ecology, 2019)
Summary A carbon footprint (CF) assessment of Chinese high‐speed railways (HSRs) can help guide further development of the world's longest HSR network. In this research, a hybrid economic input‐output and life cycle assessment (EIO‐LCA) method was applied to estimate the CF of the Beijing‐Shanghai HSR line. Specific CFs were analyzed of different subsystems of the line, different stages of production, and three calculation scopes. Results showed that the annual CF of the Beijing‐Shanghai HSR is increasing, whereas the per‐passenger CF constantly declined between 2011 and 2014. Scope 1 emissions account for an average of 4% of the total annual CF, Scope 2 contribute 71%, and Scope 3 comprise 25%. Among the different stages, operation contributes the largest (71%), followed by construction (20%) and maintenance (9%). In the construction stage, the bridges have the largest CF, followed by trains, and then rails. A trade‐off exists between the increase in carbon emissions due to construction of bridges and the reduction in operation emissions affected by leveling changes in terrain. The Beijing‐Shanghai HSR line has a relatively higher per‐passenger CF than eight other HSR lines, which is largely due to China's coal‐based carbon‐intensive energy mix of electricity generation, high proportion of bridges, higher operating speed, and heavier train body. In the future, cleaner electricity supply options, more efficient raw material production, and improvement of trains are keys to reducing the CF of Chinese HSRs.

NK cells play a significant role in immunosurveillance at the early stage of MLL-AF9 acute myeloid leukemia via CD226/CD155 interactions - YaJie Wang; Chen Chen; Fang Dong; ShiHui Ma; Jing Xu; YueMin Gong; Hui Cheng; Yuan Zhou; Tao Cheng; Sha Hao (Science China Life Sciences, 2015)